Globus pallidus internus-deep brain stimulation for Lance Adams syndrome post-COVID-19: A case report and systematic review - Amir Reza Bahadori; Parisa Javadnia; Mohammad Amin Fathollahi; Afshan Davari; Sajad Shafiee; Aidine Omidvar; Sara Mohammadian; Sara Ranji; Abbas Tafakhori (Interdisciplinary Neurosurgery, 2025)
Objects: Lance Adams syndrome (LAS) is a chronic post-hypoxic myoclonus that predominantly arises following successful cardiopulmonary resuscitation; however, there are so rare instances following respiratory failure. Method: This report discusses a 42-year-old female patient who developed myoclonus after COVID-19 and was diagnosed with LAS. She received globus pallidus internus-deep brain stimulation (Gpi-DBS). A systematic review following PRISMA guidelines was also conducted across multiple databases for post-hypoxic myoclonus patients who underwent DBS until November 30. Result: The systematic review comprised eight studies focusing on post-hypoxic myoclonus, four explicitly diagnosed with LAS. All but one underwent Gpi-DBS. Improvement in myoclonus scores following DBS treatment was noted in all cases. In our case, not only were myoclonus symptoms significantly improved, but there was also an enhancement in the patient’s quality of life assessments. Conclusion: DBS should be considered a safe and effective therapeutic strategy for patients diagnosed with LAS who resist conventional pharmacotherapy.